Expanding Existing Antimicrobial Stewardship Programs in Pediatrics: What Comes Next. (18th December 2017) - Kronman, Matthew P; Banerjee, Ritu; Duchon, Jennifer; Gerber, Jeffrey S; Green, Michael D; Hersh, Adam L; Hyun, David; Maples, Holly; Nash, Colleen B; Parker, Sarah; Patel, Sameer J; Saiman, Lisa; et al.
Abstract : The prevalence of pediatric antimicrobial stewardship programs (ASPs) is increasing. We review strategies for ASPs to adapt and report standardized metrics, expand activities to specialized populations, and implement novel diagnostics for continued progress in improving antibiotic use and patient outcomes. Abstract: The prevalence of pediatric antimicrobial stewardship programs (ASPs) is increasing in acute care facilities across the United States. Over the past several years, the evidence base used to inform effective stewardship practices has expanded, and regulatory interest in stewardship programs has increased. Here, we review approaches for established, hospital-based pediatric ASPs to adapt and report standardized metrics, broaden their reach to specialized populations, expand to undertake novel stewardship initiatives, and implement rapid diagnostics to continue their evolution in improving antimicrobial use and patient outcomes.